An uncertainties simulation model applied to an automated laminar flowmeter - Pedro, António (2020)
Aircraft oxygen regulators are a normally used specialized test bench designed to perform tests to the regulators during its work conditions. The tests are performed placing the regulator in the barometric chamber, where low pressure conditions are forced to simulate altitude conditions and then a flow is forced on the output of the regulator to simulate the inhalation of the user. The relevant test flows are measured by laminar flowmeters. These flowmeters are meant to measure the flowrate at pressures correspondent to altitudes between sea level altitude and fifty thousand feet. In this work a way was studied to automate laminar flowmeters used on oxygen regulator test benches. For this purpose, was developed a data acquisition system (DAS) using a microcontroller board and two microelectromechanical systems-MEMSs (a pressure and temperature sensor and a differential pressure sensor). Since these MEMSs did not have factory calibration, they were calibrated in this study. The automated flowmeter was also calibrated. To estimate the error of flow rate measured by this solution, an uncertainties simulation model based on the Monte Carlo method and several calibrations were performed. According to the automated flowmeter calibration, the uncertainty obtained (0.45% fs) is accepted, but the authors only recommend its use for actual volumetric flowrate measurements.